Treatment of dental implant displacement into the maxillary sinus - An, Jun-Hyeong (Maxillofac Plast Reconstr Surg, 2017)
BACKGROUND: Displacement of dental implants into the maxillary sinus is rare, but it primarily occurs in patients with severe pneumatization of the maxillary sinus and/or deficiency of the alveolar process. Some complications such as the infection of the paranasal sinuses and formation of the oroantral fistula can be followed by the displacement of a dental implant. Therefore, the displaced implant has to be removed immediately with surgical intervention show and another plan for rehabilitation should be considered. MAIN BODY: The conventional procedure for the removal of a displaced implant from the maxillary sinus involves sinus bone grafting and new implant placement performed in two or more steps with a significant time gap in between. Simplification of these surgical procedures can decrease the treatment duration and patient discomfort. CONCLUSIONS: In this review, we discuss the anatomical characteristics of the maxillary sinus and the complications associated with implant displacement into the sinus.